REVIEW ON LOCAL GOVERNMENT REVENUE: TRENDS AND CHALLENGES - Suzei Mat Nurudin; Zarina Mohd Zain (International Journal of Accounting, Finance and Business, 2023)
This article is aimed at reviewing the relevant works of literature from previous studies and research which are related to the trends and challenges on local government revenue in Malaysia through the google scholar application. Using such an application, the authors have found 186 articles on the topic concerning local government in Malaysia. Among the trends and challenges that were often highlighted in local government revenue include local government collection tax arrears and also the provision of efficient services. Listed by the Ministry of Housing and Local Government, the revenues of local government are the assessment tax, licenses & permits, rentals, government grants, car parking charges, planning fees, compounds, fines, interest, and loans. Over the years there are some trends and challenges faced by local government in dealing with the revenue. This article is focused on 28 articles from 186 found in analyzing the trends and challenges that affected local government revenue